ELEMENTS OF IMPRESSIONISM AS CONSTITUENTS OF FICTIONAL THINKING IN ROSTYSLAV YENDYK’S PROSE - Залевська, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
On the material of collections «Zov zemli», «V zudari z zhyttiam», «Zhaha» the article analyses the peculiarities of Rostyslav Yendyk’s individual-authorial style, particularly his gravitation towards the impressionistic manner of writing. The attention is concentrated on the internal world of the heroes, their feelings and impressions.